196k views
5 votes
Р

с
о
1.
Convert the following equation to standard form: y = -3x + 2
— у = 2
3х + y = 2
о 3х + y = -2
о — 3 — у. = 2
ОО
в

User Pierpy
by
5.5k points

1 Answer

0 votes

9514 1404 393

Answer:

3x +y = 2

Explanation:

Standard form is ...

ax +by = c

where a, b, c are mutually prime integers and the leading coefficient is positive.

We can put the equation in this form by adding 3x to both sides.

y = -3x +2

3x +y = 2 . . . . . add 3x to both sides. This is standard form.

User Somebodysomewhere
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.